Health care seeking behaviours of mother having under 24 months old child attending Outpatient Department of Tribhuvan University Teaching Hospital, Kathmandu - Uprety, Kamala (Journal of Chitwan Medical College, 2018)
Health care seeking behaviour of a mother has an important role in reducing morbidity and mortality related common childhood illness amongst under-five children. The main objective of this study was to identify the health care seeking behaviour of mothers who attended tertiary level hospital in Kathmandu for common childhood illness. The study was conducted in the paediatrics out-patient department of Tribhuvan University Teaching Hospital Kathmandu by employing a descriptive design under the quantitative research approach. Similarly, a non-probability convenience sampling technique was used in the study in which 151 mothers having 0-24 months (0-2 years old) children attending in OPD were included. Prior to data collection, written approval of the proposal was obtained from Research Department and Institutional Review Board, Institute of Medicine and Director of TUTH. The data were collected with the help of interview schedule and analyzed by using descriptive statistics. Result of this study found that 85.4% mothers had information regarding common childhood illness. All respondents were found seeking care when their children got sick. Out of the total respondents, 90% of them took their children in health facility whereas remaining 10% took their children to the traditional healer for treatment. Out of the total respondents taking their children in health facility, 80.8% mentioned that the children’s condition was worsened and, among them 65.4% preferred government health facility. Reason for not taking to health facilities were far distance, expensive treatment, lack of money, lack of faith and mothers’ perception of severity of illness. From this study, it can be concluded that the service provided through government health facilities needs to be improved and focus should be given on health education to mother regarding common childhood illness and its severity. Likewise, it is also necessary to increase mothers’ positive attitude and perception toward medical treatment when a child gets sick.